Investigating Translation Notions with Reference to Selected Ayahs from the Glorious Qur'an - HAITHAM MAHDI MAATOQ Al-TAMEEMI ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The complexity  in the Glorious Quran causes difficulty to comprehend the stylistic elements of the SL through translating into English. The important of the paper is to recognize some stylistic notions as translated into English . Samples of  Ayahs have been selected. Three translators have been chosen from different backgrounds. The comparison is made among the translations (eight text) based on conveying the original features of the text. Out of the present study, it is concluded that acceptability and adequacy are perceived in all the translated texts. Nevertheless, Pickthall  adheres  accuracy, archaism, and cohesion of the original more than others in his translation